2022
DOI: 10.1111/jmwh.13332
|View full text |Cite
|
Sign up to set email alerts
|

Women Electing Oocyte Cryopreservation: Characteristics, Information Sources, and Oocyte Disposition: A Systematic Review

Abstract: Introduction:Recently, there is a growing interest in cryopreservation for nonmedical reasons, widely known as planned oocyte cryopreservation. This review aims to summarize and understand the characteristics of women who undergo or consider planned oocyte cryopreservation, identify their initial sources of information, and describe the oocyte disposition. This information should assist health professionals with shared decisionmaking.Methods: A systematic review was performed and reported following the Preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Most of our participants were highly educated, and some had received health-related training. Whilst these characteristics are consistent with women who consider EEF ( Inhorn et al , 2018 ; Giannopapa et al , 2022 ; Sandhu et al , 2023a ), they may influence the capacity for knowledge gain from the Decision Aid. In fact, at baseline, both cohorts showed a moderate understanding of EEF and age-related infertility, which could explain why no group differences were observed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Most of our participants were highly educated, and some had received health-related training. Whilst these characteristics are consistent with women who consider EEF ( Inhorn et al , 2018 ; Giannopapa et al , 2022 ; Sandhu et al , 2023a ), they may influence the capacity for knowledge gain from the Decision Aid. In fact, at baseline, both cohorts showed a moderate understanding of EEF and age-related infertility, which could explain why no group differences were observed.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, there was a 120% rise in egg freezing across other European countries between 2016–2019 ( Wyns et al , 2020 ; Smeenk et al , 2023 ). Increased utilization of EEF coincides with greater availability and public awareness coupled with considerable media attention ( Ethics Committee of the American Society of Reproductive Medicine, 2018 ; Platts et al , 2021 ; Giannopapa et al , 2022 ). In addition, regulatory changes to gamete storage time limits in the UK, and the introduction of EEF in France and Singapore ( De Proost and Johnston, 2022 ; UK Government, 2022 ; Chin et al , 2023 ), means that more women are considering the option.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients who decide to proceed with OC and are included in these studies are highly educated and have high household incomes. 46 This may limit the generalizability of these results to the entire U.S. population. For example, one cross-sectional survey of 1,000 women that assessed attitudes toward elective OC found that Asian race, single status, holding employment, household income greater than or equal to $125,000, and a history of infertility were associated with an increased likelihood of considering OC.…”
Section: Discussionmentioning
confidence: 96%